(untitled) (Journal of Event, Tourism and Hospitality Studies, 2024)
To fulfil the required credit hours for graduation, all final semester students in the Event Operation Certificate (EOC) program offered by Pasir Salak Community College are required to undergo industrial training. Aside from improving students’ existing skills, industrial training stands as the main platform to develop their talents, ultimately helping them towards secured employment in the events industry. However, rapid technological changes and development in the events industry have resulted in a mismatch between knowledge and skills. The theoretical knowledge and skills acquired at the educational institutions often demonstrate a disparity with the practical applications within industries. Hence, the purpose of this study was to investigate the role of industrial training in enhancing the employability of EOC graduates post-graduation. The study employed a qualitative approach via a case study design. Purposive sampling was used to recruit the respondents based on their knowledge and experience to answer the research questions. The sample consisted of 11 EOC graduates from Pasir Salak Community College and three employers with experience in training EOC students during the industrial training period. The data was collected through in-depth interviews using semi-structured questions. All interview sessions were audiorecorded and transcribed verbatim for thematic analysis by coding and identifying recurring themes. The findings revealed that the majority of EOC graduates who underwent industrial training were given multiple tasks by employers in preparing themselves for future employability in the events sector. The graduates also acquired various new skills from the industrial training, including digital skills. However, most EOC graduates faced challenges throughout their industrial training, encompassing time limitations, physical exhaustion, communication obstacles, and unexpected mental strain. Meanwhile, employers prioritize negotiation within communication, technical training, and event concepts during industrial training and value digital skills as a bonus for graduates entering the workforce. Overall, they see industrial training as a platform for sparking interest, fostering positivity, and encouraging graduates to venture into the events business.